Penerapan Metode Tilawati dan Hypnoteaching Dalam Proses Pembelajaran Al-Quran di TPA Ali Adam Coper Ponorogo - Sa’adah, Fibriana Miftahus (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
In the process of learning the Koran, teachers are also required to always be active and creative in applying learning methods. One learning method that attracts students' attention is tilawati, this method uses classical reading and listening. In this teaching method, it is combined with hypnoteaching. This research aims to determine the application of hypnoteaching and tilawati in the Al-Quran learning process at TPA ALI ADAM CoperJetis Ponorogo. This research uses a qualitative approach and the type of research used is descriptive research. There are three data collections, namely interviews, observation and documentation. The data analysis model used is Miles and Huberman which goes through three stages, namely data condensation, data presentation and conclusion drawing. The results of this research found that the application of tilawati and hypnoteaching in the Al-Quran learning process at TPA ALI ADAM Coper Jetis Ponorogo was carried out with a combination of the two which used two techniques, the first technique (tilawati) was classical which used the technique of the teacher reading the students listening, the teacher reading the students imitation, students and teacher read together (using props). In this technique, hypnoteaching is also applied in the form of (intention, pacing, leading, positive words, praise, modeling and comprehensive understanding of the material). The second technique is reading and listening (using a tilawati reading book). In this technique, hypno teaching is applied the same as the classical technique.